Exploring work-life balance among professional women in mainland China: A qualitative study - Pan, Ying; Sun, Gong (Frontiers in Psychology, 2022)
This article introduces a qualitative study utilizing semi-structured interviews to explore the barriers and resources of professional women to attain work-life balance (WLB) in the context of mainland China. Interviews were conducted with full-time employed women who had received higher education and possessed professional qualifications (N = 20). The findings reveal underlying factors in work and non-work domains which influence the achievement of work-life balance among Chinese professional women. Participants were found to perceive and attain their work-life balance differently according to their personal traits. The findings also highlight social and family support resources for Chinese professional women from the perspective of Confucianism. This study contributes to current knowledge on work and life issues through the lens of professional women's work-life balance perceptions and experiences in mainland China.